“I Want to Be Heard”: Rape Victims’ Encounters With Swedish Police - Rudolfsson, Lisa (Violence against women, 2024)
Interactions with police are vitally important to victims’ ability to process their trauma. This study focused on the experiences of victims who reported a rape to police in Sweden. Thirteen women participated in interviews; the material was analyzed using inductive thematic analysis. Findings include lack of information and the role of luck in finding an understanding officer; some found comfort, and some felt violated once again. Long processing times bound participants to their trauma. Findings highlight the need for improved knowledge of trauma among police, victims’ needs for information and rights to support, and structural barriers that need to be addressed.